2018
DOI: 10.1002/jhet.3300
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Ring Transformation of Bis‐oxadiazoles to Bis‐thiadiazoles and Investigation of Their Anticancer Activities

Abstract: A new series of 2,6‐dimethyl‐4‐phenyl‐N′3,N′5‐bis(3‐phenyl‐1,3,4‐thiadiazol‐2(3H)‐ylidene)‐1,4‐dihydropyridine‐3,5‐dicarbohydrazides were synthesized from reaction of 5,5′‐(2,6‐dimethyl‐4‐phenyl‐1,4‐dihydropyridine‐3,5‐diyl)bis(1,3,4‐oxadiazole‐2‐thiol) or diethyl 2,2′‐(2,6‐dimethyl‐4‐phenyl‐1,4‐dihydropyridine‐3,5‐dicarbonyl)bis(hydrazine‐1‐carbodithioate) with various hydrazonoyl chlorides. The structures of new compounds were established on the basis of their elemental analysis and IR, 1H NMR, and mass spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Thus, many researchers orchestrated their efforts to formulate and construct novel bioactive bis -heterocycles as antiviral agents and other therapeutic effects. It has been reported in the literature that compounds containing bis -thiadiazole cores have attracted considerable interest in the area of drug discovery due to their potential as antihypertensive α -blocking [ 5 ], antimicrobial [ 6 , 7 , 8 ], and anticancer [ 9 , 10 ] agents. In addition, bis -thiazole pharmacophores were reported to reveal various biological activities such as anti-inflammatory, analgesic, anti-ulcerogenic [ 11 ], antiviral [ 12 ], antimicrobial [ 13 , 14 ], antioxidant [ 15 ], and anticancer activities [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, many researchers orchestrated their efforts to formulate and construct novel bioactive bis -heterocycles as antiviral agents and other therapeutic effects. It has been reported in the literature that compounds containing bis -thiadiazole cores have attracted considerable interest in the area of drug discovery due to their potential as antihypertensive α -blocking [ 5 ], antimicrobial [ 6 , 7 , 8 ], and anticancer [ 9 , 10 ] agents. In addition, bis -thiazole pharmacophores were reported to reveal various biological activities such as anti-inflammatory, analgesic, anti-ulcerogenic [ 11 ], antiviral [ 12 ], antimicrobial [ 13 , 14 ], antioxidant [ 15 ], and anticancer activities [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, bis-thiazoles are known for their remarkable biological activities, having anticancerous, antibiotic, antimicrobial, antifungal, antibacterial, tuberculostatic, antiamoebial and anti-inflammatory activities [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…1,4-Dihydropyridines are important class of compounds in the field of pharmaceuticals and drugs. Researches on dihydropyridine and its synthetic analogs has revealed that they possess many biological activities such as vasodilates, antihypertensive, antiinflammatory, anti-ischemic agents, antianginal, antithrombotic, anticonvulsant, antimicrobial activities (11)(12)(13)(14)(15)(16)(17)(18). Moreover, many heterocyclic hydrazones represents an interesting class of hetero compounds with a broad spectrum of biological activities, analgesic, anti-inflammatory, antimicrobial, antitubercular, antiplatelet, anticonvulsant, antimalarial and antiviral activities (19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%